(untitled) (Bulletin KNOB, 1991)
Wagenaar was the last of medieval architects rather than a terminal point of Neo-Gothic. Those who were able to follow the restoration of the churches of Utrecht from close by learnt to know Wagenaar as a man of thorough research, a man of joy on the smallest historic detail and the man of the conscientiously working out of proposals for architect and restoration-committee. His proposals certainly were built up from a ’gothic’ creativity adaptable to each decade of all of those centuries and to all of the local variants on Gothic architecture. This bibliography of his written works is desirable for his texts as much as his beautiful drawings which form an indisoluble part of his publications. His works are of the greatest importance to everyone who is interested in the Gothic style or concerned with the research or restoration of a medieval building.